Comparison of analgesic methods by using ropivacaine after arthroscopic shoulder surgery - ŞİRİN, EVRİM; BEZER, MURAT (Springer Verlag, 2014)
Background: There is no clinical study which has evaluated real effectiveness of ropivacaine when it is used in a subacromial pump in addition to its bolus injection in a mixture of agents. The aim of the study is to evaluate pain relieving effect of ropivacaine infusion by a pain pump after arthroscopic shoulder surgery. Method: Thirty-six patients were randomly divided into three groups. Arthroscopic subacromial surgery was performed under general anesthesia. A subacromial catheter was placed in groups 1 and 2 patients. At the end of the operation, 15 ml of 0.5 % ropivacaine, 15 mg of ketolorac, and 4 mg morphine sulfate mixture was applied to all patients into the subacromial space. In addition to that, group 1 patients were applied with 0.5 % ropivacaine running through a pain pump at 4 cm3/h. Group 2 patients only received 100 cm3 saline (placebo) through the same pain pump, which was also running at 4 cm3/h. No additional intervention except subacromial mixture application was performed in group 3. Pain levels were evaluated by using the visual analogue scale. Results: Twelve male and 19 female patients were included in this study. During the first postoperative hour, there was no difference between the groups in terms of pain scores. During the ongoing 24-h period, group 2 patients suffered less pain and had less analgesic need compared with the other two groups (p < 0.05). However, in the same day, there was no significant difference in pain scores and analgesic consumption between groups 1 and 3 (p > 0.05). Conclusion: In terms of pain relief, the mixture of morphine, ropivacaine, and ketolorac was found to be as effective as the 24-h pump infusion of ropivacaine following arthroscopic rotator cuff repair. It was observed that placebo-given patients suffered less pain because saline increased the long-term effect of ropivacaine. So if an appropriate analgesic agent is applied to the subacromial space, there is no need for a pump infusion postoperatively. © 2013 EFORT.
Keywords: Arthroscopy; Infusion pump; Ropivacaine; Shoulder; Subacromial